INTERNSHIP MAHASISWA PRODI TADRIS BAHASA INGGRIS DI SEKOLAH SUKMA BANGSA LHOKSEUMAWE MELALUI PROGRAM "SEA" - Nurul Fadhillah; Fadhlur Rahman; Salmina Elvia Amanda; Siti Hajar (Jurnal Abdimas Bina Bangsa, 2024)
Students' English Activity (SEA), a collaboration between the Department of English and Sekolah Sukma Bangsa (SSB) Lhokseumawe, supports numerous studies showing internship programs' benefits. To achieve positive change, all SEA program participants must actively participate in this service activity, so the Participatory Action Learning System (PALS) was employed. The main purpose of community service program is intended to help English department students advance their careers by guiding them down a successful professional path. English students actively participate in various critical stages of the SEA program, contributing directly to core activities and addressing specific challenges faced by Sekolah Sukma Bangsa students. Their participation extends beyond simple planning, demonstrating a commitment to creating meaningful and impactful learning experiences. This active participation marks a watershed moment in the students' lives, transforming them from passive students to proactive contributors. The program's vision relies on this collaborative approach to align with Sekolah Sukma Bangsa goals and encourage co-creation of educational projects. This nuanced and contextually feasible execution is facilitated by the collaborative foundation between English education students and school stakeholders, emphasizing the importance of a cooperative and mutually beneficial partnership